Development issues transition and change (Vol.2) - Pfeffer,Georg (ed.); Behera,Deepak Kumar (ed.) (New Delhi, 1997)
While examining the current literature on tribal India we notice an amazing absence of anthropological studies based on long term fieldwork in a large and important section of the Indian population. The series-Contemporary Society: Tribal Studies-tries to fill in this gap and thereby attempts to overcome our ignorance on many aspects of tribal society. Presented under two volumes the contributions are from sixty-four anthropologists and sociologists from Asia, Europe and America. The first volume, consisting of twenty-five chapters, is devoted to the study of structural and ethnic issues, gender, ageing, ecology and ideology in contemporary tribal society. The chapters in the Second Volume, thirty-three in number, deal with developmental issues, transition and change in various sectors of Tribal Life. Contributors to both the volumes offer specimen of their regular interest.
Keywords: Tribal women